Sequências didáticas inéditas e introdução à esperança matemática aplicadas em cursos pré-vestibulares - Freitas, Felipe Grilli (Universidade Federal de São Carlos, 2019)
In the routine of the pre-university courses one tends to work, in a year, the diverse contents which are studied in high school, often giving greater depth or emphasis on some subjects. There are already well-qualified students, others less. Some students, dedicated to studies for some years, and knowledgeable of most of the questions of previous exams, need to settle and deepen for, besides fixing questions, completing them in short intervals of time; others have a contact much more superficial and initial with the contents incident on the great university entrance exams. In this sense, this work presents sequences of teaching composed of questions written by the author, worked on the methodology of didactic engineering, applied for the revision of several fundamental contents for the university entrance exams ENEM, FUVEST, UNESP, UNICAMP and UNIFESP, in all your phases, aiming to improve the diferent levels of student's knowledge . In addition, there is an introduction, through problems, to the concept of statistical hope. Therefore, this work proposes to present activities with unpublished questions, in forms attractive to develop the classes and possibilities to present a new mathematical concept for students.
Keywords: Ensino de Matemática; Prática docente; Esperança matemática; Teaching of mathematics; Teaching Practice; Expected Value; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO